MECHANISM AND DIRECTIONS OF APPLYING TAX INCENTIVES IN THE NATIONAL TAX SYSTEM - Tukhsanov Kudratillo Nozimovich (Modern American Journals, 2025)
This article discusses tax incentives and preferences, which are the subject of much debate in tax affairs. The characteristics, similarities, and differences of tax benefits and preferences and their application in the tax system are comparatively analyzed.
Keywords: business entities, micro-firms, small enterprises, individual entrepreneurs, regression correlation, linear regression model, econometric modeling, multifactor econometric model, correlation matrix, determination coefficient.